Economic assessment for compressed air energy storage business model alternatives - Matos, Catarina R. (2023)
Compressed air energy storage (CAES) is a large-scale energy storage system with long-term capacity for utility applications. This study evaluates different business models’ economic feasibility of CAES pre-selected reservoir case studies. It assesses several scenarios for each case study and analyzes two business models: one for the storage of excess renewable energy sources (RES) and another for energy arbitrage. The novelty of this work is performing the economic investment assessment using a Monte Carlo Simulation (MCS) methodology applied to CAES, considering the uncertainties associated with such types of projects and evaluating different business models for the technology. The results suggest a better performance from the CAES RES business model than the CAES arbitrage business model. Furthermore, the diabatic CAES assessed scenarios seem to have more attractive results than their equivalent adiabatic CAES systems in the CAES RES business model. However, adiabatic CAES can be economically feasible in both business models. In addition, it was observed that CAES is viable in specific scenarios and can be profitable for the storage of energy from RES, facilitating the management of their variability, decreasing their dependence on weather, and helping their integration into the grid. However, CAES does not seem a good fit for grid energy arbitrage in the generality of the scenarios evaluated.